Among the wild chimpanzees [videorecording] - Jampel, Barbara; Kane, Dennis; Skinner, Thomas (National Geographic Society special, 1984)
Documents Jane Goodall's twenty-two-year field research on the wild chimpanzees of East Africa. Shows the chimpanzees' nomadic behavior, their family structure, and their ability to hunt and make and use tools. Also looks at discoveries of warfare and cannibalism.